NEW DEFINITIONS OF MYOCARDIAL INFARCTIONS (COMMENTS ON “UNIVERSAL DEFINITIONS OF MYOCARDIAL INFARCTION” PUBLISHED IN №5, 2008) - A. V. Shpector; E. Yu. Vasilyeva (Рациональная фармакотерапия в кардиологии, 2016)
New definitions of myocardial infarctions (comments on “Universal definitions of myocardial infarction” published in №5, 2008)